2022
DOI: 10.3390/molecules27072204
|View full text |Cite
|
Sign up to set email alerts
|

Target Design of Novel Histone Deacetylase 6 Selective Inhibitors with 2-Mercaptoquinazolinone as the Cap Moiety

Abstract: Epigenetic alterations found in all human cancers are promising targets for anticancer therapy. In this sense, histone deacetylase inhibitors (HDACIs) are interesting anticancer agents that play an important role in the epigenetic regulation of cancer cells. Here, we report 15 novel hydroxamic acid-based histone deacetylase inhibitors with quinazolinone core structures. Five compounds exhibited antiproliferative activity with IC50 values of 3.4–37.8 µM. Compound 8 with a 2-mercaptoquinazolinone cap moiety disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
(53 reference statements)
0
4
0
1
Order By: Relevance
“…Autodock4 is a common docking tool with approximately 6000 citations since 2009 [ 57 ]. This program is an open-source package that can predict the binding affinity and dock pose of ligands toward a specific protein target [ 58 ]. It has been reported by Gohlke et al that ligand partial charge calculated using the PM6 method has been shown to greatly increase the docking accuracy and cluster population of the most accurate docking [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Autodock4 is a common docking tool with approximately 6000 citations since 2009 [ 57 ]. This program is an open-source package that can predict the binding affinity and dock pose of ligands toward a specific protein target [ 58 ]. It has been reported by Gohlke et al that ligand partial charge calculated using the PM6 method has been shown to greatly increase the docking accuracy and cluster population of the most accurate docking [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a pair of HDAC6-selective inhibitors with 2-mercaptoquinazolinone as the cap moiety were drawn for the first time. This design foresaw manipulating the surface recognition group (quinazolinone core as a cap) and linker while retaining the hydroxamic acid side chains at the C-2 or N-3 position [218]. In a recent investigation, HDAC inhibitors featuring 4-acyl pyrrole caps were employed as a scaffold for developing potent hybrid inhibitors that target both bromodomain and extra-terminal (BET) proteins as well as HDACs [219].…”
Section: Molecular Modelingmentioning
confidence: 99%
“…In the quest for HDAC6-selective inhibitors, a series of compounds incorporating 2-mercaptoquinazolinone as the cap moiety were developed. This effort focused on modifying the surface recognition group (utilizing the quinazolinone core as a cap) and linker, while preserving hydroxamic acid side chains at either the C-2 or N-3 position [218]. Recently, researchers have explored various avenues to design HDAC6-selective inhibitors.…”
Section: Achieving Selectivity For Each Hdac Isoformmentioning
confidence: 99%
“…Đặc biệt gần đây, một loạt các dẫn xuất của N-hydroxycinnamamide dựa trên cấu trúc của belinostat đã được chúng tôi tổng hợp cho thấy hiệu quả mạnh mẽ, khả năng hiệp đồng chống lại sự tăng sinh của dòng tế bào đa u tuỷ, và ức chế HDAC mạnh mẽ [18]. Trong một nghiên cứu khác, chúng tôi cũng đã cố gắng thiết kế một loạt các dẫn xuất cho khả năng ức chế chọn lọc enzyme HDAC6 sử dụng 2-mercaptoquinazolinone làm nhóm nhận diện bề mặt [19]. Tiếp nối các kết quả nghiên cứu trên, trong nghiên cứu lần này chúng tôi đã thiết kế và tổng hợp một số các hợp chất dựa trên N-hydroxycinnamamide và mở rộng thêm một vài hợp chất N-hydroxybenzamide mang các đơn vị liên kết amide (Hình 1e) nhằm bổ sung vào kho dữ liệu các hợp chất có khả năng ức chế HDAC tiềm năng.…”
Section: Mở đầU *unclassified